Assessing the Feasibility of Small-Scale RDF Technology in Urban Solid Waste Management Using Cost-Benefit Analysis - Purwanto, Heru; Nurhasana, Renny; Rohimah, Azizah (Advance Sustainable Science Engineering and Technology, 2025)
The development of Waste Processing Facilities based on the 3R principles (TPS 3R) with small-scale Refuse Derived Fuel (RDF) technology in Jakarta aims to support waste sorting, composting, reuse, and recycling activities, with locations strategically placed as close as possible to service areas. However, its implementation faces significant challenges, particularly due to high initial investment and operational costs. This study evaluates the feasibility of four TPS 3R facilities using a Cost-Benefit Analysis approach, considering economic, environmental, and social dimensions. The results indicate that all units are economically viable, with TPS 3R Joe demonstrating the highest economic feasibility, marked by a BCR of 1.870, an NPV of IDR 25.81 billion (USD 1.60 million), and an IRR of 15.76%. The study concludes that the successful implementation of small-scale RDF technology is highly influenced by technical efficiency, institutional support, community participation, and policies that are adaptive to local characteristics.